Case Report of Management of Increased Intracranial Pressure in Epidural Hematoma - Putra, Rikki Oktrian; Imran, Yudhisman; Rahmansyah, Mulia; Khusfiani, Triasti; Putri, Mustika Anggiane; Az zahra, Ainaya (CoinReads Media Prima, 2024)
Epidural haematoma (EDH) is an abnormal collection of blood between the bone and the dura mater. A 26-year-old male was brought by his family to the Hospital Emergency Department with complaints of headache after a traffic accident. The patient was unconscious for 5 minutes and had one seizure. After the seizure, the patient regained consciousness and complained of headache and vomiting. Neurological status examination was within normal limits. CT-Scan examination of the head found a linear fracture accompanied by a picture of epidural haemorrhage (EDH) 59.34 cc in the right parietal, and midline shift to the left. The patient received conservative management in the form of mannitol. The patient also underwent operative management in the form of decompressive craniotomy for haematoma evacuation. This case describes a patient with EDH with symptoms of increased intracranial pressure and received medical and operative management.